Numerical investigation of the effect of slope angle and height on the stability of a slope composed of sandy soil - Taher, Nichirvan Ramadhan; Gör, Mesut; Aksoy, Hüseyin Suha; Awlla, Halmat Ahmed (Gumushane University, 2022)
Slope stability issues are very frequently in civil engineering applications and are commonly encountered in huge and significant projects such as dams, highways and tunnels, etc. This study examines the impact of slope height (H) and slope angle (?) on the stability of loose granular soil slope underlined by dense granular soil layer. For this purpose, a number of finite element analyses were conducted on a full-scale soil slope. The computer program Plaxis 2D code was used which is based on the finite element method (FEM). The granular soils were described by non-linear hardening soil model, which is an advanced elastoplastic stress-strain constitutive soil model. Six different slope angles were investigated and for each angle, six different heights were chosen. In total, twelve series of numerical analyses were executed. In the first six series, it was assumed that there is no surcharge load on the top of the slope. In the second six series, the effect of surcharge load was also investigated. According to numerical analysis results, it was found that the slope height and slope angle have a considerable effect on the safety factor (FS) of the slope. It was also noticed that most of the failure surfaces of the slope were circular and classified as face slope failure. It was observed that by increasing slope height and the slope angle, the FS of the slope decreases and vice versa. In addition, curves and charts have been proposed to easily estimate the FS of loose granular soil slope. © 2022, Gumushane University. All rights reserved.
Kumlu zeminden oluşan bir şevin stabilitesine şev açısı ve yüksekliğinin etkisinin sayısal olarak incelenmesi
Keywords: Loose granular soil; Plaxis 2D; Safety factor; Slope angle; Slope stability